2019
DOI: 10.1002/jssc.201900504
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and green microextraction of organophosphorus flame retardants by a novel phosphonium‐based deep eutectic solvent

Abstract: Based on the solidification of a hydrophobic deep eutectic solvent in air‐assisted liquid phase microextraction combined with gas chromatography and mass spectrometry, a green and sustainable microextraction technique was developed for extracting, separating, and detecting organophosphorus flame retardants in aqueous samples. In this study, some strategies were considered for overcoming or improving the challenges of conventional solvent microextraction procedures. In addition, a hydrophobic deep eutectic solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It could be found that increasing the salt concentration in a solution increases its ionic strength and, thus, typically decreases the analyte solubility in the aqueous solution. This behavior can be justified by considering the salting‐out phenomenon [33]. Therefore, analytes migration to the extraction phase improved, and consequently, the EE increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be found that increasing the salt concentration in a solution increases its ionic strength and, thus, typically decreases the analyte solubility in the aqueous solution. This behavior can be justified by considering the salting‐out phenomenon [33]. Therefore, analytes migration to the extraction phase improved, and consequently, the EE increased.…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, the selected DES as the extracting media was added to the solution followed by intensive shaking of the solution by using a vortex agitator for an optimal time. After centrifugation of the sample, the extraction phase, including the analytes, was removed from the solution with the aid of a widened bell-shaped device and then it was frozen by placing the vial with the bell-shaped device in an ice bath [33]. The solidified DES transferred to a microtube was then ready for final analysis after melting.…”
Section: Methodsmentioning
confidence: 99%
“…The method exhibited acceptable recoveries of 83–117% and also demonstrated high precision (%RSD < 10%). HDESs were also reported in the DLLME-SFOD for the extraction of aromatic amines [ 44 ] and OPFRs [ 16 ] from aqueous samples.…”
Section: Dess In Dllme-sfodmentioning
confidence: 99%
“…This technique is known as DLLME-SFOD. Since its development, DLLME-SFOD has found applications as the preconcentration for different analytes from various matrices [ 16 , 17 , 18 ]. Most of the solvents that are used in DLLME-SFOD have lower toxicity than the ones that are conventionally used in DLLME [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…That's why researchers have made many developments in the DLLME method to solve these problems. Recently, methods such as vortex, ultrasonic, pH, and temperature changes are used to increase the contact surface and dispersion of the extraction solvent, and the disperser solvent is no longer used [23][24][25]. Also, deep eutectic solvents (DESs) have been extensively developed as an extractant in the DLLME method.…”
Section: Introductionmentioning
confidence: 99%